Students ‘Attitude Towards the Utilization of Google Classroom for Learning - Charles Olabode Olumorin; Ebenezer Omolafe Babalola; Sunday Ashaolu; Eyiyemi Veronica Omolafe (Indonesian Journal of Educational Research and Technology, 2022)
This study investigates students' attitudes towards the use of Google Classroom for learning at the University of Ilorin, Nigeria. Descriptive survey research is used in this study. The population for this study consisted of all students at the University of Ilorin, Nigeria. The population of this study consisted of undergraduates in ten selected faculties at the University of Ilorin. Samples were taken using a multi-stage sampling technique. Use of stratified sampling technique to divide the population into strata based on faculty. Then, random sampling technique was used to select 30 respondents from each stratum. Specifically, 30 undergraduate students were selected from ten faculties, bringing the total number of respondents to 300 people. The research finding is that students have a positive attitude towards the use of Google Classroom at the University of Ilorin. Gender has no significant effect on student attitudes towards the use of Google Classroom at Ilorin University. The research course did not have a significant effect on respondents' attitudes towards the use of Google Classroom at the University of Ilorin. The study concludes that Google Classroom's diverse potential can be harnessed and harnessed to transform teaching and learning processes from traditional chalk-talk methods to virtual or blended learning, which is increasingly recognized as a global best practice in the university field. It is recommended that University lecturers be encouraged to use Google Classroom because of the many benefits it has for teaching and learning.